2023
DOI: 10.3390/plants12020331
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Links between Flowering and Abiotic Stress Response: A Focus on Poaceae

Abstract: Extreme temperatures, drought, salinity and soil pollution are the most common types of abiotic stresses crops can encounter in fields; these variations represent a general warning to plant productivity and survival, being more harmful when in combination. Plant response to such conditions involves the activation of several molecular mechanisms, starting from perception to signaling, transcriptional reprogramming and protein modifications. This can influence the plant’s life cycle and development to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 165 publications
(205 reference statements)
1
2
0
Order By: Relevance
“…Notably, these HSPs were identified exclusively at the transcriptomic or proteomic level, strongly suggesting the involvement of HSPs in SA-induced flowering through post-transcriptional regulation. These results also established possible molecular connections between flowering and abiotic stresses as recently proposed ( Chirivi and Betti, 2023 ).…”
Section: Discussionsupporting
confidence: 84%
“…Notably, these HSPs were identified exclusively at the transcriptomic or proteomic level, strongly suggesting the involvement of HSPs in SA-induced flowering through post-transcriptional regulation. These results also established possible molecular connections between flowering and abiotic stresses as recently proposed ( Chirivi and Betti, 2023 ).…”
Section: Discussionsupporting
confidence: 84%
“…Under moderate drought, plants adopted a drought avoidance strategy; that is, they tended to delay flowering and reduce RGR as a form of adaptation to limited energy availability. In other studies, plants adopting this strategy showed reduced water loss through transpiration and minimal metabolic activity (Chirivì and Betti 2023;Toscano et al 2019).…”
Section: Effect Of Drought Stress On Flowering Timementioning
confidence: 81%
“…Plants generally respond to drought stress by delaying flowering and reducing growth to adapt to limited energy availability (Chirivì and Betti 2023;Toscano et al 2019). In a different strategy, drought-stressed plants induce early flowering to complete their life cycle and overcome unfavorable environmental conditions (Franks 2011;Sivakumar and Srividhya 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The horticultural crop industry is economically important and the lifeline of world food security [3]. Due to their intolerant nature, horticultural crops cannot endure abiotic stresses and are more affected than agronomic crops [4]. The quality of horticultural products is negatively impacted by abiotic stressors that occur during postharvest handling [5].…”
Section: Introductionmentioning
confidence: 99%